(w,c)-Almost Periodic Generalized Functions - Khalladi, Mohammed Taha; Kostić, Marko; Rahmani, Abdelkader; Velinov, Daniel (Sarajevo Journal of Mathematics, 2022)
The aim of this work is to introduce and study a new space of ( w,c) -almost periodic generalized functions containing the ( w,c) - almost periodic functions, ( w,c) -almost periodic Schwartz distributions, the algebra of periodic generalized functions, the space of Bloch-periodic generalized functions as well as the space of ( w,c) -periodic generalized functions.